Identification of key factors conquering developmental arrest of somatic cell cloned embryos by combining embryo biopsy and single-cell sequencing - Liu, Wenqiang (Cell Discov, 2016)
Differentiated somatic cells can be reprogrammed into totipotent embryos through somatic cell nuclear transfer. However, most cloned embryos arrest at early stages and the underlying molecular mechanism remains largely unexplored. Here, we first developed a somatic cell nuclear transfer embryo biopsy system at two- or four-cell stage, which allows us to trace the developmental fate of the biopsied embryos precisely. Then, through single-cell transcriptome sequencing of somatic cell nuclear transfer embryos with different developmental fates, we identified that inactivation of Kdm4b, a histone H3 lysine 9 trimethylation demethylase, functions as a barrier for two-cell arrest of cloned embryos. Moreover, we discovered that inactivation of another histone demethylase Kdm5b accounts for the arrest of cloned embryos at the four-cell stage through single-cell analysis. Co-injection of Kdm4b and Kdm5b can restore transcriptional profiles of somatic cell nuclear transfer embryos and greatly improve the blastocyst development (over 95%) as well as the production of cloned mice. Our study therefore provides an effective approach to identify key factors responsible for the developmental arrest of somatic cell cloned embryos.